2019
DOI: 10.1002/bjs.11161
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a gene expression test to identify hard-to-heal chronic venous leg ulcers

Abstract: Background Chronic venous leg ulcers pose a significant burden to healthcare systems, and predicting wound healing is challenging. The aim of this study was to develop a genetic test to evaluate the propensity of a chronic ulcer to heal. Methods Sequential refinement and testing of a gene expression signature was conducted using three distinct cohorts of human wound tissue. The expression of candidate genes was screened using a cohort of acute and chronic wound tissue and normal skin with quantitative transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
1
18
0
Order By: Relevance
“…Currently, it is unclear if genetic alterations in a number of identified genes are causal or associations. Certainly, this area of research is interesting and requires further study in larger population-based studies and determination that early intervention in identified and affected individuals with specific venous gene polymorphic variants would benefit from interventions to correct venous hemodynamics and prevent VLU formation [180][181][182][183][184]. Important principles to prevent and reduce recurrent VLU are following adopted principles of timely referral to a vascular specialist, evaluation and ultrasonography, treating infection and debridement, appropriate compression, and appropriate interventions when indicated [1].…”
Section: Approaches To Prevent Ulcer Occurrence and Recurrencementioning
confidence: 99%
“…Currently, it is unclear if genetic alterations in a number of identified genes are causal or associations. Certainly, this area of research is interesting and requires further study in larger population-based studies and determination that early intervention in identified and affected individuals with specific venous gene polymorphic variants would benefit from interventions to correct venous hemodynamics and prevent VLU formation [180][181][182][183][184]. Important principles to prevent and reduce recurrent VLU are following adopted principles of timely referral to a vascular specialist, evaluation and ultrasonography, treating infection and debridement, appropriate compression, and appropriate interventions when indicated [1].…”
Section: Approaches To Prevent Ulcer Occurrence and Recurrencementioning
confidence: 99%
“…The WD14 gene signature was created using three cohorts of patients: screening, validation and study cohorts (ethical approval numbers: 04/WSE02/10; SJT/C617/08; 09/WSE02/51). 11 A longitudinal cohort study was performed comprising of 85 consecutive patients referred to a tertiary wound healing unit, as previously described by Bosanquet et al in 2012 and therefore the methods will be only briefly reviewed herein. 12 Patients with chronic wounds consistent with underlying venous disease were diagnosed by a senior wound healing physician at a tertiary wound healing centre.…”
Section: Methodsmentioning
confidence: 99%
“…The methods used in genetic analysis have been described in detail previously. 11 Patients in the study cohort had their VLU wound edge biopsy WD14 gene signature score calculated and dichotomised into a 'healing' or 'non-healing' genotype at baseline. After 12 weeks, wounds were clinically assessed and classified as 'healing' if there was a reduction in wound size or 'non-healing' if they were static or deteriorating.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations